Profil Leukosit, Diferensial Leukosit, dan Indeks Stres Luwak Jawa (Paradoxurus hermaphroditus) (LEUCOCYTE COUNT, LEUCOCYTE DIFFERENTIATION, AND STRESS INDEX OF COMMON PALM CIVETS (PARADOXURUS HERMAPHRODITUS) - Satyaningtijas, Aryani Sismin; Kusumorini, Nastiti; Fachrudin, Moh. Mursyid; ., Purnomo (Jurnal Veteriner, 2015)
Common palm civets (Paradoxurushermaphroditus) have a potential to be commercial commodityanimal which produce best coffee, parfume, but also as reservoir potential infection desease such as SevereAcute Respiratory Syndrome (SARS). Therefore, their health status is very important. This study wasaimed to discribe the leukocyte profile, and stress index of 4 males Java common pal civets and 4 females.Blood sampling was taken from vena femoralis and done at weeks 1st, 5th, 6th, and 7th. Leukocyte profilewere examined using haemocytometerand blood smear. The average leukocyte count of males and femalescommon palm civets per mm3 were (3.33±0.86)x103 and (2.83±0.70)x103, neutrophil were (1.01±0.47)x103and (0.68±0.30)x103, eosinophil were (0.16±0.18)x103 and (0.04±0.05)x103, lymphocyte were (2.06±0.42)x103and (2.05±0.59)x103, monocyte were (0.09±0.06)x103 and (0.06±0.06)x103. Stress index were (0.49±0.18)for males and (0.37±0.22) for females. Generally, leukocyte count of males Java common palm civet werehigher than those of females.
Keywords: Paradoxurushermaphroditus, leukocytes, differentiatial leukocyte, stress index